2020
DOI: 10.5039/agraria.v15i1a6638
|View full text |Cite
|
Sign up to set email alerts
|

Citrullus lanatus morphophysiological responses to the combination of salicylic acid and salinity stress

Abstract: The salinity of irrigation water is one of modern agriculture's major obstacles, as it can damage the plants metabolism and, consequently, its development. Currently there is a great demand for substances that may mitigate such effects, such as salicylic acid. Thus, this study aimed to evaluate the effects of salicylic acid application on watermelon plants (Citrullus lanatus L.) under salinity stress. The experimental design was a randomized block design, in an incomplete factorial scheme, with four replicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In a study with watermelon cv. Crimson Sweet using a mixture of soil and organic compost, in a 1:1 ratio, Ribeiro et al (2020) observed that the increase in irrigation water salinity reduced the internal CO 2 concentration, leading to the lowest value under water with electrical conductivity of 4.0 dS m -1 .…”
Section: Resultsmentioning
confidence: 99%
“…In a study with watermelon cv. Crimson Sweet using a mixture of soil and organic compost, in a 1:1 ratio, Ribeiro et al (2020) observed that the increase in irrigation water salinity reduced the internal CO 2 concentration, leading to the lowest value under water with electrical conductivity of 4.0 dS m -1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, this effect varies depending on the species, application methods, SA concentration, and growing environments. Ribeiro et al [30] evaluated watermelon characteristics in relation to water S and SA exogenous treatment and observed that the SA did not alleviate the detrimental impact of salinity but rather that it positively enhanced the plant morphophysiology up to the concentration of 0.85 mM. In light of the aforementioned discussions, the SA foliar spray produced thicker leaflets in bean plants due to the increment in the lamina's thickness at midvein.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is variation of this effect in species, forms of application and concentration of SA and cultivation conditions. In the study by Ribeiro et al (2020), when evaluating morphophysiological aspects of watermelon as a function of salinity in water and exogenous application of SA, found that the acid did not mitigate the deleterious effect of salinity, however, it beneficially increased the morphophysiology of plants up to a dosage of 0.85 mM. However, Rafique et al (2011), in the cultivation of pumpkin seedlings, when soaking the seed with SA, observed that the protein content and activities of the protease and nitrate reductase enzymes were significantly influenced with concentrations of 30 mg L -1 of SA and that the soaking of the seed mitigates the adverse effects of salt stress on the initial growth of pumpkin.…”
Section: Methodsmentioning
confidence: 98%
“…The minimum (−α) and maximum (α) values ranged, respectively, from 0.5 to 4.5 dS m −1 and 0.0 to 1.5 mM, totaling 9 treatments (Table 1), with four replicates, making up 36 experimental plots, each plot consisting of three plants. Salicylic acid concentrations were based on previous experiments with other vegetables (Silva et al, 2019;Ribeiro et al, 2020). The electrical conductivities in the irrigation water were based on the threshold salinity of the crop (Dias et al, 2016).…”
Section: Methodsmentioning
confidence: 99%